PENERAPAN PERLAKUAN KHUSUS PEREMPUAN DAN ANAK TERHADAP PENANGANAN PERKARA KEKERASAN DALAM RUMAH TANGGA OLEH KEJAKSAAN (Studi Kasus Kejaksaan Tinggi Riau) - Windy Putri Priyatmi; Erdianto Erdianto; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Domestic Violence is a classic problem in the world of law and gender. Eventhough the legal umbrella to protect victims from domestic violence already exists,namely Law Number 23 of 2004 concerning the Elimination of Domestic Violence, thishas not been enough to anticipate this violence, in this case the need for attention andlegal protection, both the government and law enforcement agencies, as well as from thecommunity so that it is expected that everyone who hears, sees, or knows about theoccurrence of domestic violence is obliged to take preventive measures and provideassistance. Actually, what are the causes and what kind of protection for women andchildren victims of domestic violence are regulated in Indonesian positive law.This type of research is sociological legal research conducted at the Riau HighCourt. The data sources used are primary data and secondary data. Data collectiontechniques were carried out by interviews and literature review. The data were analyzedqualitatively which produced descriptive data and concluded with a deductive thinkingmethod.The result of this study is that access to justice is provided through formal andnon-formal channels. Through formal channels, providing access that fully prioritizes theinterests of women and children, in this case the prosecutor's office which plays a veryimportant role. Meanwhile, through informal channels, cases involving women andchildren, both as perpetrators and as victims, can be resolved through customarymechanisms or deliberations. The scope of the Prosecutor's Guideline Number 1 of 2021Concerning Access to Justice for Women and Children in handling this case is thehandling of criminal cases involving women and children who come into contact with thelaw at the stages of investigation, investigation, pre-prosecution, prosecution,examination at trial courts and implementation of court decisions that has obtainedpermanent legal force. Then the obstacles faced by the Attorney General's Office inprotecting women and children victims of domestic violence, namely the facilities tosupport the implementation of Law Number 23 of 2004 concerning the Elimination ofDomestic Violence are inadequate, such as special closed counseling rooms, so that itwill make it comfortable for victims to tell stories .Keywords: Domestic Violence - Attorney.